COLOUR EXCESSES OF 74 SUPERGIANTS AND 30 CLASSICAL CEPHEIDS - Kovtyukh, V. V.; Soubiran, C.; Belik, S. I.; Yasinskaya, M. P.; Chehonadskih, F. A.; Malyuto, V. (Одеські астрономічні публікації, 2007)
We derive accurate, homogeneous atmospheric parameters (Teff , log g, Vt, [Fe/H]) for 74 FGK non-variable supergiants and for 30 classical cepheids in 302 pulsation phases based on the highresolution, high signal-to-noise echelle spectra. The extremely high precision of the effective temperature determination (10-30 K) is achieved by using the line- depth ratio method. These parameters are correlated with unreddened B-V colour index compiled from the literature for investigated stars to obtain an empirical relationship of the form (B-V )0 = 57.984 - 10.3587(logTeff )2 + +1.67572(logTeff )3 - 3.356logg + 0.0321Vt+ +0.2615[Fe/H] + 0.8833(logg)(logTeff ) This expression have been used for the estimation of the colour excesses E(B-V) of individual supergiants and classical cepheids with an error 0.05 mag, which matches precision of the most sophisticated photometric techniques. The application range is F0-K0, luminosity classes I and II. Considering the large distances of supergiants, this method opens up a possibility for the large-scale extinction mapping of the Galaxy, with sensitivity down to 0.1-0.2 mag.